Customization in educational computer games and its effect on learning: Experimental study with primary school children. (19th July 2021) - Javora, Ondřej; Děchtěrenko, Filip; Tetourová, Tereza; Volná, Kristina; Brom, Cyril
Abstract: The instructional effects of customization features in child learning games have rarely been examined. This value‐added study addresses the existing gap with regards to user‐initiated cosmetic customization of environment elements (i.e., non‐avatar customization). Participants ( N = 143; M age = 9.41) studied a biological topic for about 20 min: either using the experimental version of a learning game with customization features, or from a control version without them. Null results were found as concerns between‐group differences: both for motivation‐related variables and learning outcome measures. These findings indicate that user‐initiated cosmetic customization features can be omitted by game designers, especially in settings where children are assigned specific instructional materials from which to study. Lay Description: What is already known: User‐initiated cosmetic customization (the term user‐initiated is afterwards left out of the text for brevity) refers to making choices about a game's visual or audio attributes without directly affecting the content of gameplay itself. Studies with non‐child learners showed that a sub‐type of cosmetic customization referred to as avatar customization (i.e., customization of learners' game characters) can be potentially beneficial for learning. The instructional efficiency of other sub‐types of cosmetic customization (i.e., customization of other elements, such as environmental ones) in game‐based learning for children is less clear. What this paper adds: Children (Grades 3–4) prefer a game with a cosmetically customizable environment over its non‐customizable counterpart: but only when they can contrast these two versions (not when they cannot contrast them). Children enjoy learning and learn equally from customizable and non‐customizable games. Implications for practice: Game‐based learning with cosmetic customization features of game's environment can be used for learning without risk of harming learning outcomes. However, when children's autonomy in choosing instructional materials is restricted, there is little need to invest in the cosmetic customization of a game's environment elements. Cosmetic customization of a game's environment elements may play a more notable role when children are able to choose learning materials.